2010
DOI: 10.1152/japplphysiol.91257.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of posture on regional pulmonary blood flow in rats as measured by PET

Abstract: Using small animal PET with 68 Ga-radiolabeled human albumin microspheres (Ga-68-microspheres), we investigated the effect of posture on regional pulmonary blood flow (PBF) in normal rats. This in vivo method is noninvasive and quantitative, and it allows for repeated longitudinal measurements. The purpose of the experiment was to quantify spatial differences in PBF in small animals in different postures. Two studies were performed in anesthetized, spontaneously breathing Wistar rats. Study 1 was designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
3
14
0
1
Order By: Relevance
“…Moreover, the HP 129 Xe images in Fig. 5 have a spatial resolution comparable to that currently achieved in small animal lungs with Single Photon Emission Tomography (SPECT) [44] and Positron Emission Tomography (PET) [45]. However, these EC infusion images were acquired within ∼20 min, representing a 4–5-fold advantage in temporal resolution over nuclear imaging.…”
Section: Resultsmentioning
confidence: 64%
“…Moreover, the HP 129 Xe images in Fig. 5 have a spatial resolution comparable to that currently achieved in small animal lungs with Single Photon Emission Tomography (SPECT) [44] and Positron Emission Tomography (PET) [45]. However, these EC infusion images were acquired within ∼20 min, representing a 4–5-fold advantage in temporal resolution over nuclear imaging.…”
Section: Resultsmentioning
confidence: 64%
“…S4), and receives *44% of the mean total lung blood flow, while the right lung, comprising *60% of the average lung mass, receives *56% of the mean total blood flow when in the supine position. 9 The RUL of the intact rat lungs receives the majority of the right pulmonary artery blood flow (33%) compared with the RML (26%), RLL (13%), and AL (28%). 28 This finding may explain our observation that the RUL receives the majority of the seeded ECs instilled in a supine position (Fig.…”
Section: Ec Distribution Follows Physiologic Blood Flowmentioning
confidence: 98%
“…Previous studies have demonstrated that the distribution of intravenously injected microspheres larger than 15 mm, similar to the size of ECs, in the pulmonary vasculature varies according to anatomical position of the rodent during injection (e.g., upright: the lungs hanging by the trachea vs. supine: the lungs laying on their back). 9 Endothelial progenitor cells, which express the a5b1 integrin, efficiently adhere to fibronectin remaining on the luminal walls of denuded large vessels in vivo. 10 A similar process might govern the adhesion of ECs to fibronectin that is found on the walls of decellularized pulmonary vasculature.…”
mentioning
confidence: 99%
“…Apart from using corner posts, where the limbs can be fixated for a reproducible position, the use of an immobilization bed has also been proposed [79]. The posture of the animal (prone or supine) can have an effect on the outcome of the imaging study has been demonstrated by Richter et al [80], where they studied regional pulmonary blood flow in rats. As mentioned previously, the position of the animal with respect to the imaging field of view can also change the data, due to factors such as DOI and resolution.…”
Section: Posturementioning
confidence: 99%